Development Strategy For The Old Town Area As Urban Herıtage Tourısm In Ternate Cıty North Maluku Provınce - Susilawati Susilawati; I Putu Anom; Yohanes Kristianto (Cita Konsultindo Research Center, 2024)
This research aims to identify and describe the development of the Old City area, analyze the role of stakeholders in the development of the Old City area, and formulate appropriate strategies for the development of the Old City area using SWOT analysis. Data collection was conducted using a qualitative approach. Methods and techniques for data collection included field observation, interviews, documentation, literature study, and informant determination techniques. The results of this study indicate that the Old City area has significant potential for historical and cultural tourism. Based on the destination life cycle, the development of the Old City area is in the Development phase. The strategies that can be formulated for the development of the Old City area include: (1) Utilization of heritage assets for educational tourism, (2) development of cultural events to increase visits, (3) optimization of Gamalama traditional market, (4) development of culinary areas, (5) optimization of transportation and accessibility, (6) establishment of a tourism management institution, (7) development of tourism facilities, (8) improvement of coordination among stakeholders, (9) preservation of the authenticity of heritage assets, (10) integrated promotion through media and events, (11) collaboration with other tourist attractions, (12) sustainable tourism management, (13) education and awareness-raising for the community, (14) advocacy for supportive policies and regulations.